[OsF6]x−: Molecular Models for Spin‐Orbit Entangled Phenomena. Issue 47 (27th July 2017) - Pedersen, Kasper S.; Woodruff, Daniel N.; Singh, Saurabh Kumar; Tressaud, Alain; Durand, Etienne; Atanasov, Mihail; Perlepe, Panagiota; Ollefs, Katharina; Wilhelm, Fabrice; Mathonière, Corine; Neese, Frank; Rogalev, Andrei; et al.
Abstract: Heavy 5d elements, like osmium, feature strong spin‐orbit interactions which are at the origin of exotic physical behaviors. Revealing the full potential of, for example, novel osmium oxide materials ("osmates") is however contingent upon a detailed understanding of the local single‐ion properties. Herein, two molecular osmate analogues, [OsF6 ] 2− and [OsF6 ] −, are reported as model systems for Os 4+ and Os 5+ centers found in oxides. Using X‐ray absorption spectroscopy (XAS) and X‐ray magnetic circular dichroism (XMCD) techniques, combined with state‐of‐the‐art ab initio calculations, their ground state was elucidated; mirroring the osmium electronic structure in osmates. The realization of such molecular model systems provides a unique chemical playground to engineer materials exhibiting spin‐orbit entangled phenomena. Abstract : Fragmenting Osmates : Probing the electronic ground state of an isolated osmium ion is a key step towards the fundamental understanding of the intricate phenomena observed in osmium oxides ("osmates"). Using X‐ray spectroscopy techniques and multi‐reference ab initio calculations, the electronic structure of two new [OsF6 ] x − molecular osmate analogues were determined as model systems for Os 4+ and Os 5+ centers found in oxides. These molecular systems offer a unique chemical approach to design materials presenting spin‐orbit entangled effects.